THE SYNTHESIS OF NIKCEL(II) COMPLEXES WITH SALYCILIDENE ANILINE LIGAND DERIVATIVES AS POTENTIAL OLED (ORGANIC LIGHT-EMITTING DIODE) COMPOUND - NURIL MARYAM (NIM : 205 10 024);Pembimbing 1 :Dr. Deana Wahyuningrum, M. Si., Pembimbing 2 : D, IRMA
Imines compounds are Schiff base family which has wide application either in Biology and Chemistry. Salicylidene aniline derivatives are one of the most common Schiff base compounds. It was produced from the condensation of anilines with salicylaldehides. The complex of metal transition with this kind of ligand has been developed extensively in catalyst, biology systems, and material chemistry. Some of complexes Nickel(II)-Salicylidene aniline have been reported as anti-bacteria and anti-microba, but the fluorescence properties have not been studied further more. Therefore in this research the complexes of Nickel(II) with salicylidene aniline derivatives, which are salicylidene p-chloroaniline and salicylidene p-toluidine ligands, were synthesized to determine its fluorescence properties. The method used in this research is the green chemistry method using environtmentally friendly solvent, low energy, and producing products with high yields. Nickel(II) complexes with salycilidene aniline ligand derivatives have been successfully synthesized utilizing Microwave Assisted Organic Synthesis method as potential OLED (Organic Light-Emitting Diode) compounds. The imine products which are (E)-2-((4-chlorophenylimino)methyl)phenol (L1) and (E)-2-((p-tolylimino)methyl)phenol (L2) were synthesized with solvent combination ethyl L-lactate:water (9:1) with chemical yields of 97% (m.p.: 98-100oC) and 96% (m.p.: 92-94oC) for L1 and L2, respectively. IR spectra showed peaks at the wavenumbers of 3500 cm-1 (-OH) and 1600 cm-1 (C=N). From MS analysis, the m/z value are 232.12 (L1) and 212.19 (L2). 1H NMR spectra indicated the hydrogen atom bonded to C=N with peak at chemical shift 8.576 ppm (L1) and 8.629 ppm (L2). The chemical shift of 13C NMR at 161.206 ppm (L1) and 161.25 ppm (L2) indicated C atom of C=N. The Nikcel(II) complexes color is light green for K1 (decomposition temperature: 190oC) and dark green for K2 (decomposition temperature: 170oC). TLC analysis using methanol:kloroform (2:1) showed different spots with Rf values of 0.78 (K1) and 0.82 (K2). From IR spectra, vibration peaks of C=N has shifted to lower frequencies from 1612 cm-1 (L1) and 1653 cm-1 (L2) to 1597 cm-1 (K1) and 1621 cm-1 (K2), caused by C-O-M bonds. Emission peak of L1 was shown at 305 nm, while L2 has two peaks at 305 nm and 514 nm. The emission spectra of K1 and K2 are different from its ligands. K1 have 3 peaks emission at 295 nm, 586 nm, and 862 nm. However K2 show more peaks at 294 nm, 351 nm, 586 nm, and 682 nm. Therefore K2 is a more potential precusor for OLED compound compare to K1.